2021
DOI: 10.1186/s12885-021-08799-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning and its associated factors among breast cancer patients on chemotherapy at Tikur Anbessa specialized hospital, Addis Ababa Ethiopia: an institution-based comparative cross-sectional study

Abstract: Background Breast cancer is the second leading cause of cancer in the world. It is the commonest type of cancer in Ethiopia. Cognitive problems are common among breast cancer patients. The study aimed to assess cognitive functioning and its associated factors among breast cancer patients at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia 2020. Methods Institution-based comparative cross-sectional study was conducted. Study subjects were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
4
0
1
Order By: Relevance
“…Thus, women with breast cancer who have lower education levels seem to have worse cognitive performance. These data corroborated the findings of a previous study that found an association between lower education level and worse Mini-Mental State Examination (MMSE) performance in women with breast cancer ( 38 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, women with breast cancer who have lower education levels seem to have worse cognitive performance. These data corroborated the findings of a previous study that found an association between lower education level and worse Mini-Mental State Examination (MMSE) performance in women with breast cancer ( 38 ).…”
Section: Resultssupporting
confidence: 91%
“…Information on participants' menopausal status was presented in 10 (50%) of the studies. Supplementary Table S2 presents information about the articles included in this review ( 6 , 23 - 36 , 38 - 41 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 The MMSE is graded on a 30-point scale. 23 Abebe et al 24 assessed cognitive function in patients with BC. The MMSE has been widely applied in cognitive studies of Chinese patients 25 - 27 and its reliability and validity have been verified previously.…”
Section: Methodsmentioning
confidence: 99%
“…Como exemplo, encontramos apenas 2 publicações com estudos sobre o CRCI em pacientes com câncer de mama realizadas do continente africano. (126,127)…”
Section: Participantesunclassified